1996
DOI: 10.1021/ja961602e
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Adsorption of a “Kinked” DNA to a Neutral Curved Surface:  Comparisons to and Implications for Nonspecific DNA−Protein Interactions

Abstract: We have examined the adsorption of different DNA sequences to mercaptoethanol-capped CdS quantum dots, ∼40 Å diameter, as a minimalist model for nonspecific protein−DNA interactions, and compared these results to what we have previously found for Cd2+-surface-rich dots of the same size (Mahtab, R.; Rogers, J. P.; Murphy, C. J. J. Am. Chem. Soc. 1995, 117, 9099). We find that neutralization of the surface leads to no detectable binding, based on our luminescence assay, for “straight” and A-tract oligonucleotide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
117
2
3

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(128 citation statements)
references
References 49 publications
6
117
2
3
Order By: Relevance
“…The particle size and distribution from our TEM studies are consistent with that of the reported value of 4.0 ( 0.6 nm. 9 However, from the TEM experiments it is also found that most of the QDs were aggregated to a larger structure of average diameter ∼150 nm (Figure 3b). The TEM image of the dialyzed QDs is shown in Figure 3c.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…The particle size and distribution from our TEM studies are consistent with that of the reported value of 4.0 ( 0.6 nm. 9 However, from the TEM experiments it is also found that most of the QDs were aggregated to a larger structure of average diameter ∼150 nm (Figure 3b). The TEM image of the dialyzed QDs is shown in Figure 3c.…”
Section: Resultsmentioning
confidence: 92%
“…Reasonably small excitation wavelength dependency of the emission spectra confirms narrow dispersion of the CdS size in the nanostructure, 19 which is in agreement with the TEM studies on the nanoassembly. 9 To understand the dynamics of excited electronhole-pair (EHP) recombination, we measured picosecondresolved PL of the QDs. Figure 5b shows picosecond-resolved transient of CdS QDs (laser excitation ) 375 nm, emission wavelength ) 500 nm), which is found to be multiexponential in nature with three decay time components (τ i ) with various preexponential values (a i ); 172 ps (83%), 1.61 ns (13%), and 21.95 ns (4%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In these experiments, the quantum dots are not particularly well passivated, but their surfaces are modified with cationic or hydrogenbonding groups that are presumably attractive to the anionic DNA polymer. Photoluminescence titrations are then performed with short DNA oligomers that are either "normal" or "unusual" in terms of local structure and flexibility (43)(44)(45)(46). The shape of the emission spectrum does not change, only its intensity.…”
Section: Quantum Dots As Fluorescent Probesmentioning
confidence: 99%
“…From these experiments, valuable biophysical insight has been gained into the way that different DNAs bind to generic protein-sized curved surfaces without the need for researchers to label the DNA or use radioactivity (43)(44)(45)(46). Some of these unusual DNA structures are correlated with human disease (47), and thus the development of this optical detection scheme is of interest to the bioanalytical community.…”
Section: Quantum Dots As Fluorescent Probesmentioning
confidence: 99%